Pembinaan keterampilan Desain Grafis Bagi Generasi Muda Di Perumahan Griya Elok Pengambiran Kota Padang - Januardi Nasir; Yasha Langitta Setiawan (Society : Jurnal Pengabdian Masyarakat, 2022)
Perum Griya Elok is located in the Arai Pinag sub-district, Lubuk Begalung sub-district, Padang city, Perum Griya Elok has a population of approximately 500 residents where these residents come from various races and ethnic religions. The younger generation who are at Perum Griya Elok tend to be unemployed due to limited knowledge and education. That's why we, the devotees, propose to provide an understanding of community service about technology that can generate money, exemplified by coaching using graphic design such as being able to use Photoshop and Coreldraw. The use of Photoshop graphic design now is very promising among being able to do photo editing for weddings, and the Coreldraw application is very promising. Among the creation of logos, posters, billboards themselves really help the youth to develop skills. To make money. With this coaching held, the youth at Griya Elok housing are able to use tools in Photoshop, and make logos with Corel Draw, where in this coaching they are given lectures with practice by providing levels for beginners. The goal is to quickly understand the use of the application where the level itself is from the beginning to the editing process to the design of the image itself.for each language can only be written in one paragraph with the format of one column.